2019 IEEE Intelligent Transportation Systems Conference (ITSC) 2019
DOI: 10.1109/itsc.2019.8917442
|View full text |Cite
|
Sign up to set email alerts
|

Anytime Lane-Level Intersection Estimation Based on Trajectories of Other Traffic Participants

Abstract: Estimating and understanding the current scene is an inevitable capability of automated vehicles. Usually, maps are used as prior for interpreting sensor measurements in order to drive safely and comfortably. Only few approaches take into account that maps might be outdated and lead to wrong assumptions on the environment. This work estimates a lanelevel intersection topology without any map prior by observing the trajectories of other traffic participants.We are able to deliver both a coarse lane-level topolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Similarly, Bastani et al [2] propose to postprocess the output of a binary segmentation model through morphological thinning and the Douglas-Peucker method. Based on simulated data, Meyer et al [16] propose a lanelevel intersection estimator, leveraging birds-eve-view tracking of traffic participants for intersection graph estimation. Li et al [11] use an RNN to build building polygons and road graphs from overhead images, while Chu et al [6] propose to iteratively build a road graph from overhead images.…”
Section: Related Work a Road Network Estimationmentioning
confidence: 99%
“…Similarly, Bastani et al [2] propose to postprocess the output of a binary segmentation model through morphological thinning and the Douglas-Peucker method. Based on simulated data, Meyer et al [16] propose a lanelevel intersection estimator, leveraging birds-eve-view tracking of traffic participants for intersection graph estimation. Li et al [11] use an RNN to build building polygons and road graphs from overhead images, while Chu et al [6] propose to iteratively build a road graph from overhead images.…”
Section: Related Work a Road Network Estimationmentioning
confidence: 99%
“…For example, in [18] [19], the authors used vehicle trajectories acquired from on-board sensor such as stereo camera or LIDAR. Later, Meyer et al used simulated vehicle trajectories and employed a Markov chain Monte Carlo sampling to reconstruct the lane topology and geometry at both real and simulated intersections [20], [21]. In [22], [23], the authors used collected GPS data loaded on fleet vehicles.…”
Section: Intersection Lane Inferencementioning
confidence: 99%
“…Unlike the indoor environments, the outdoor environment is less affected by a Manhattan world assumption [20], research for modeling the outdoor layout has been done [21]- [25]. Jo and Sunwoo [21] and Alvarez et al [22] modeled the parameterized roadmap for autonomous car driving using the linear interpolation of points from the trajectory of the road or B-spline curve fitting.…”
Section: Related Workmentioning
confidence: 99%
“…Geiger et al [23] proposed a probabilistic model for multi-object traffic scene understanding of video input sequences that jointly infers the urban scene layout as well as the position and orientation of moving objects using visual evidence. Meyer et al [25] suggested the generalized version of road layouts of Geiger's work run in real-time.…”
Section: Related Workmentioning
confidence: 99%